Meios convencionais e não convencionais de proteção ao meio ambiente do trabalho - Liberatti, Guilherme (2016)
The purpose of this research is to discuss the means of monitoring and supervision of human fundamental rights, including the right to a healthy and ecologically balanced workplace, provided through conventional (treaty-monitoring bodies) and unconventional means (special procedures). The search initially elucidate the evolution of recognition of human rights to its universalization. This essay will spell the emergence of environmental standards internationally, as well as the recognition of the right to a healthy and ecologically balanced workplace as a fundamental human right. It will also address the gradual universalization and internationalization of worker protection and the inevitable interconnection between labor rights and the environment. It also will elucidate the monitoring and supervisory of these rights, by regular and conventional means/procedures, and either, through special and unconventional means/procedures. While conventional means have their conditional implementation of the ratification of specific international legal instruments by states and have cogent and binding force, some unconventional means are effected through resolutions of political bodies such as the Human Rights Council of the United Nations (UN) or the Governing Body of the International Labour Organization (ILO) and use political and moral sanctions. In addition, other non-conventional means of voluntary nature, such as social clause in trade agreements, corporate codes of conduct for transnational corporations, social labeling programs, collaborative integration between the International Labour Organization, International Monetary Fund, World Bank and World Trade Organisation also play an important role in safeguarding labor minimum standards. To achieve the objectives outlined, the research uses bibliographic method, consulting printed documents, such as books; articles and theses, and virtual documents, such as treaties; conventions; resolutions; codes of conduct; guidelines and decisions of international bodies such as the United Nations, International Labour Organization, the Human Rights Council, Economic and Social Council, and others.